Pulmonary infection by Mycobacterium riyadhense: first case report in United Arab Emirates - Sawan, Batool A.; Saleh, Leen O.; Al Shaltouni, Dina Z.; Sawan, Mohammad A.; Gawish, Shefa; Ahmed, Samar; Gomez-Seco, Julio; Otim, Michael E. (Frontiers in Medicine, 2024)
Mycobacterium riyadhense is an emerging slowly growing species that belongs to the group of nontuberculous mycobacteria (NTM) with approximately 20 cases reported worldwide. We highlight the first case of pulmonary infection by Mycobacterium riyadhense in United Arab Emirates (UAE). A 44-year-old female presented with chronic productive cough; a bronchial breathing pattern was appreciated on auscultation of her right upper lung. She was treated multiple times with allergic medications and antibiotics. Thorough investigations revealed Mycobacterium riyadhense and antitubercular drugs were started, eventually she was cured, however she had multiple relapses later. This case report holds a significant potential to make considerable contribution to the diagnosis of NTM, primarily because it presents the first documented case in UAE, as well as insights on how to address possible similar cases in the future.